Sistem Pendukung Keputusan Pemilihan Hotel Di Jakarta Dengan Menggunakan Algoritma Naïve Bayes - Agus Safarudin; Muhtajuddin Danny (Teknik Informatika, Universitas Pelita Bangsa, 2019)
Jakarta has a nickname of a metropolitan city, but many residents are still confused about choosing a place to stay or just stop by as a place to rest. To determine the decision, the writer implements the Naïve Bayes algorithm. So that with the decision support system using the Naïve Bayes algorithm the writer can be sure and made easier in determining hotel selection in Jakarta. Keywords: Sistem Pendukung keputusan, Decision Support System, Naïve Bayes